The Effect of Internet Slack on Learning Performance - Ignatius Novianto Hariwibowo (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2019)
In the midst of the widespread application of the internet in learning activities, this research was conducted to assess the impact of internet abuse on classroom learning outcomes. Published research shows the impact of diverse internet uses and this study aims to show the consequences of internet abuse on learning outcomes. This research was conducted on accounting class students with a hybrid learning system, where learning is done face-to-face in class but is supported by e-learning technology. The respondents of this study were 224 accounting students. Data were taken using questionnaires and 216 questionnaires were processed using SEM-PLS. The results of this study indicate that internet abuse does not moderate the influence of interaction and social presence on classroom learning performance. These findings indicate that internet abuse is not a factor that decreases student learning performance and can be an input for the design of e-learning concepts to use the internet as an interactive learning media where activities can still be controlled.